2018
DOI: 10.1016/j.ajo.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival and Intrascleral Vasculatures Assessed Using Anterior Segment Optical Coherence Tomography Angiography in Normal Eyes

Abstract: OCTA is a promising tool for evaluating conjunctival and intrascleral vasculatures. It may also help in understanding ocular surface blood flow relevant to vascular and ocular surface diseases, as well as aqueous humor outflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 43 publications
3
95
1
1
Order By: Relevance
“…However, using OCTA and incorporating quantitative assessment for the graft reperfusion after CAG transplantation, at different depths, has not been reported, especially in longitudinal study design as in this present study. Unlike the previous OCTA study on normal conjunctiva, 18 in which the border between the conjunctival and scleral tissues could not be delineated, the visible CAG margin in the present study provided us clear information for the depth sectioning at the CAG level or underlying episcleral level. Understanding the structure and vascularization of pterygium and the graft reperfusion after surgery helps to evaluate the risks for recurrence 19 and graft health.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, using OCTA and incorporating quantitative assessment for the graft reperfusion after CAG transplantation, at different depths, has not been reported, especially in longitudinal study design as in this present study. Unlike the previous OCTA study on normal conjunctiva, 18 in which the border between the conjunctival and scleral tissues could not be delineated, the visible CAG margin in the present study provided us clear information for the depth sectioning at the CAG level or underlying episcleral level. Understanding the structure and vascularization of pterygium and the graft reperfusion after surgery helps to evaluate the risks for recurrence 19 and graft health.…”
Section: Discussionmentioning
confidence: 62%
“…1 Our group has previously demonstrated the use of OCTA to evaluate the fibrovascular structure in pterygium. 8 Similarly, Akagi and associates 18 presented the feasibility of imaging conjunctival vasculature using swept-source OCTA in 10 normal participants in a cross-sectional study. However, using OCTA and incorporating quantitative assessment for the graft reperfusion after CAG transplantation, at different depths, has not been reported, especially in longitudinal study design as in this present study.…”
Section: Discussionmentioning
confidence: 99%
“…The number of eyes had to be limited in this explorative study due to the intense computational requirements to process several terabytes of data in millions of confocal images. Canalogram studies of human eyes suggested a perilimbal, proximal vessel network with a density [15] similar to that of porcine eyes [16][17][18][19] . We hypothesized that an RSCM analysis of the lectin-labeled outflow tract of human eyes would match our findings in porcine eyes.…”
Section: Introductionmentioning
confidence: 82%
“…These results indicate that human eyes not only have far fewer collector channels but that their anatomy differs fundamentally by spanning several clock hours and having a 50% greater CSA. This came as a surprise because recent lower resolution canalogram studies of perilimbal outflow structures suggested a density and function of outflow vessels in human eyes [15] similar to that in porcine eyes [16][17][18][19] . The smaller number, longer course, and flatter, collapsible nature of CCs in human eyes may increase the risk of outflow failure and IOP elevation in glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…23 Small series have demonstrated proof-of-principle in iridal, corneal and conjunctival tissue. [24][25][26] Most commercially-available OCTA devices do not support the full range of image acquisition and analysis modes for the anterior segment that were developed for retinal images, however, and obtaining good image quality can therefore be challenging. 27 Using OCTA of the anterior segment, Skalet et al demonstrated vascular patterns in pigmented lesions of the iris and found a difference in vascular density between three iris nevi and three iris melanomas.…”
Section: Introductionmentioning
confidence: 99%